Outcome of retrograde intrarenal surgery in the management of urolithiasis in a tertiary care centre in North India - Sharma, Ankitkumar; Dhar, Tanisha (International Surgery Journal, 2022)
Background: Nephrolithiasis is the most common presenting pathology to the urology clinic. Retrograde intrarenal surgery (RIRS) has made the treatment of upper ureteral and renal calculi a relatively atraumatic affair. We undertook a study to analyse the outcomes of RIRS performed at our institute. Methods: All patients undergoing RIRS at Government Medical College and Associated Hospitals, Jammu from November 2015 to October 2016 were included in the study population and the data prospectively collected. Patients were followed up till 6 months. Results: 62 patients underwent the procedure during the study period. Majority of the patients were of the younger age group with 56.45% patients being females. 41.9% (n=26) patients had ureteric calculi which were pushed back while 12.9% (n=8) patients had concurrent ureteral and renal calculi. One patient had a malrotated kidney with calculus, which could be cleared. The median stone size was 12 mm (range 7-18 mm). 87% were stone free at the end of the procedure. 6% procedures had to be abandoned, and 6% patients underwent follow on extracorporeal shock wave lithotripsy (ESWL). The overall stone free rate was 93.54%. The mean post-operative pain score was 2.8. Five patients developed post-operative pyelonephritis and none developed ureteric injury, avulsion or collection. At 6 months, no patient had stone recurrence or hydronephrosis. Conclusions: RIRS is a relatively safe procedure with good stone clearance. Minimal post-operative pain, with >90% stone clearance make it the cornerstone in the management of renal calculi. Our study shows that RIRS can be safely performed with minimal long term complications.